Marketing Strategies in Attracting The Interest of Export Fish Suppliers in UD. Awang Jaya Bengkulu City - Nopriadi Nopriadi; Meiffa Herfianti; Ermy Wijaya (Journal of Indonesian Management, 2021)
The research objective was to determine the marketing strategy in attracting the interest of export fish suppliers at UD. Awang Jaya of Bengkulu City. The sample in this study were 30 people consisting of 6 employees of UD. Awang Jaya Kota Bengkulu for internal factors and 24 people for external factors, namely customers from UD. Awang Jaya of Bengkulu City. The analysis method used was SWOT analysis consisting of the Internal Strategy Factor Matrix (IFAS) and the External Strategy Factor Matrix (EFAS). The value of the strength possessed by UD. Awang Jaya of Bengkulu City amounted to 21.90 minus the weakness value of 11.60, so that the IFAS value of 10.30 was obtained. The opportunity value of the marketing strategy is 20.05 and the threat is 10.90, so the EFAS value is 9.15. If the two values are combined in the IE matrix then both support quadrant I an aggressive strategy. The aggressive strategy that can be developed by UD. Awang Jaya of Bengkulu city, namely to increase promotion so that export fish suppliers are interested in selling their fish to UD. Awang Jaya and improve the quality of export fish so that customers remain loyal to order export fish to UD. Awang Jaya. The SWOT matrix analysis obtained from the research results supports the Strengths-Opportunity (SO) strategy. The SO strategy should be carried out by UD. Awang Jaya of Bengkulu City in order to maintain the trust of export fish suppliers, continue to buy all fish from export fish suppliers, keep prices stable, always on time in payments and larger fish/castor storage places.